1996
DOI: 10.1172/jci118491
|View full text |Cite
|
Sign up to set email alerts
|

Role of endogenous ceruloplasmin in low density lipoprotein oxidation by human U937 monocytic cells.

Abstract: Oxidation of lipids and lipoproteins by macrophages is an important event during atherogenesis. Activation of monocytic cells by zymosan and other agonists results in the release of multiple oxidant species and consequent oxidation of LDL. We now show evidence that ceruloplasmin, a copper-containing acute phase reactant, is secreted by zymosan-activated U937 monocytic cells, and that the protein has an important role in LDL oxidation by these cells. In one approach, ceruloplasmin has been shown to exhibit oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 55 publications
3
35
0
Order By: Relevance
“…RNAse protection experiments using probes derived from the coding region of murine ceruloplasmin revealed that this larger transcript was not due to variations within the coding region (data not shown). Ceruloplasmin transcripts were detected in splenic reticuloendothelial cells concentrated in the marginal zones of the periarteriolar lymphoid sheets, consistent with data demonstrating ceruloplasmin gene expression in rat macrophages and human macrophage cell lines (39,40). In the spleen, these cells are responsible for the efflux of iron into the plasma after phagocytosis and digestion of senescent erythrocytes.…”
Section: Discussionsupporting
confidence: 87%
“…RNAse protection experiments using probes derived from the coding region of murine ceruloplasmin revealed that this larger transcript was not due to variations within the coding region (data not shown). Ceruloplasmin transcripts were detected in splenic reticuloendothelial cells concentrated in the marginal zones of the periarteriolar lymphoid sheets, consistent with data demonstrating ceruloplasmin gene expression in rat macrophages and human macrophage cell lines (39,40). In the spleen, these cells are responsible for the efflux of iron into the plasma after phagocytosis and digestion of senescent erythrocytes.…”
Section: Discussionsupporting
confidence: 87%
“…Oxidation was terminated by addition of BHT (40 M) and DTPA (100 M) and dialysis against PBS containing DTPA (100 M). Oxidation of LDL by ceruloplasmin-bound copper was performed as described (33).…”
Section: Methodsmentioning
confidence: 99%
“…Ceruloplasmin is a serum ferroxidase that contains greater than 95% of the copper found in plasma (Hussein et al 2012) and is involved in cellular pro-oxidant and antioxidant processes (Ehrenwald & Fox 1996).…”
mentioning
confidence: 99%